Novel Diagnostic Approaches for Assessment of the Clinically Negative Neck in Head and Neck Cancer Patients - Driessen, Daphne A. J. J.; Dijkema, Tim; Weijs, Willem L. J.; Takes, Robert P.; Pegge, Sjoert A. H.; Zámecnik, Patrik; van Engen-van Grunsven, Adriana C. H.; Scheenen, Tom W. J.; Kaanders, Johannes H. A. M. (Frontiers in Oncology, 2021)
In head and neck cancer the presence of nodal disease is a strong determinant of prognosis and treatment. Despite the use of modern multimodality diagnostic imaging, the prevalence of occult nodal metastases is relatively high. This is why in clinically node negative head and neck cancer the lymphatics are treated “electively” to eradicate subclinical tumor deposits. As a consequence, many true node negative patients undergo surgery or irradiation of the neck and suffer from the associated and unnecessary early and long-term morbidity. Safely tailoring head and neck cancer treatment to individual patients requires a more accurate pre-treatment assessment of nodal status. In this review, we discuss the potential of several innovative diagnostic approaches to guide customized management of the clinically negative neck in head and neck cancer patients.